Deactivation of nitrogen donors in silicon carbide - Schmid, Frank; Pensl, Gerhard; Bockstedte, Michel Georg; Mattausch, Alexander; Pankratov, Oleg; Ohshima, T.; Itoh, H.; Weber, Heiko B.; Reshanov, Sergey (Physical Review B, 2006)
Hexagonal SiC is either co-implanted with silicon (Si+), carbon (C+), or neon (Ne+) ions along with nitrogen (N+) ions or irradiated with electrons (e-) of 200 keV energy. During the subsequent annealing step at temperatures above 1450°C a deactivation of N donors and a reduction of the compensation are observed in the case of the Si+/N+ co-implantation and e- irradiation. The N donor deactivation is investigated as a function of the concentration of the co-implanted species and the annealing temperature. The formation of energetically deep defects is analyzed with deep level transient spectroscopy. A detailed theoretical analysis based on the density functional theory is conducted; it takes into account the kinetic mechanisms for the formation of N interstitial clusters and (N-vacancy) complexes. In accordance with all the experimental results, this analysis distinctly indicates that the (NC) 4 - VSi complex, which is thermally stable at high temperatures and which has no level in the band gap of 4H-SiC, is responsible for the N donor deactivation. © 2006 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2006.nat.dphy.IAP.LAP.deacti

Doping of 4H-SiC with group IV elements - Krieger, Michael; Rühl, Maximilian; Sledziewski, Tomasz; Ellrott, Günter; Palm, Theresa; Weber, Heiko B.; Bockstedte, Michel Georg (Materials Science Forum, 2016)

Dynamical Simulation of Electron Transfer Processes in Alkanethiolate Self-Assembled Monolayers at the Au(111) Surface - Prucker, Veronika; Rubio-Pons, Oscar; Bockstedte, Michel Georg; Wang, Haobin; Brana Coto, Pedro; Thoss, Michael (Journal of Physical Chemistry C, 2013)
Electron transfer is investigated in a series of self-assembled monolayers (SAMs) consisting of nitrile-substituted short chain alkanethiolate molecules adsorbed at the Au(111) surface. Using first-principles methods and a model electron transfer Hamiltonian, we analyze the main factors controlling, at the molecular level, the electron injection times from donor states localized at the tail group of the SAM into the Au(111) substrate. We show that the donor-acceptor electronic couplings depend significantly on the orbital symmetry of the donor state and the length of the aliphatic spacer chain of the SAM. The dependence on the donor state symmetry and on the molecular structure of the linker can be used to control the electron injection times even in situations where the energy separation between the donor states is smaller than their width. © 2013 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2013.nat.dphy.ITP.ppem.dynami

Effect of crystallization on the electronic and optical properties of archetypical porphyrins - Malcioglu, Osman; Bechis, Irene; Bockstedte, Michel Georg (Physical Chemistry Chemical Physics, 2020)
Thin porphyrin films as employed in modern optical devices or photovoltaic applications show deviating electronic and optical properties from the gasphase species. Any understanding of the physical origin may pave way to a specific engineering of these properties via ligand or substituent control. Here we investigate the impact of crystallization of prototypical porphyrins on the electronic levels and optical properties in the framework of density functional theory and many-body perturbation theory. Crystallization substantially shrinks the HOMO-LUMO gap based on polarization effects. We find a shift of the HOMO to higher energy is consistent with recent experiment of MgTPP multilayer film on Ag (100) [A. Classen et al., Phys. Rev. B, 2017, 95, 115414]. Calculated excitation spectra demonstrate a significant redshift of excitation bands except for the Q bands. These lowest excitation bands, in stark contrast to the strong HOMO-LUMO gap renormalization, remain essentially the same as in the gas phase. Our work underlines the possibility of band-gap engineering via ligand-controlled modification of the polarizability.
CRIS-Team WoS Importer:2020-03-27

Electrical Charge State Manipulation of Single Silicon Vacancies in a Silicon Carbide Quantum Optoelectronic Device - Widmann, Matthias; Niethammer, Matthias; Fedyanin, Dmitry Yu; Khramtsov, Igor A.; Rendler, Torsten; Booker, Ian D.; Ul Hassan, Jawad; Morioka, Naoya; Chen, Yu Chen; Ivanov, Ivan G.; Son, Nguyen Tien; Ohshima, Takeshi; et al. (Nano Letters, 2019)
Color centers with long-lived spins are established platforms for quantum sensing and quantum information applications. Color centers exist in different charge states, each of them with distinct optical and spin properties. Application to quantum technology requires the capability to access and stabilize charge states for each specific task. Here, we investigate charge state manipulation of individual silicon vacancies in silicon carbide, a system which has recently shown a unique combination of long spin coherence time and ultrastable spin-selective optical transitions. In particular, we demonstrate charge state switching through the bias applied to the color center in an integrated silicon carbide optoelectronic device. We show that the electronic environment defined by the doping profile and the distribution of other defects in the device plays a key role for charge state control. Our experimental results and numerical modeling evidence that control of these complex interactions can, under certain conditions, enhance the photon emission rate. These findings open the way for deterministic control over the charge state of spin-active color centers for quantum technology and provide novel techniques for monitoring doping profiles and voltage sensing in microscopic devices.
CRIS-Team Scopus Importer:2019-10-18
Keywords: materials science; multidisciplinary; nanotechnology; semiconductors

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Impact of Electron Solvation on Ice Structures at the Molecular Scale - Bertram, Cord; Auburger, Philipp; Bockstedte, Michel Georg; Staebler, Julia; Bovensiepen, Uwe; Morgenstern, Karina (Journal of Physical Chemistry Letters, 2020)
Electron attachment and solvation at ice structures are well-known phenomena. The energy liberated in such events is commonly understood to cause temporary changes at such ice structures, but it may also trigger permanent modifications to a yet unknown extent. We determine the impact of electron solvation on D2O structures adsorbed on Cu(111) with low-temperature scanning tunneling microscopy, two-photon photoemission, and ab initio theory. Solvated electrons, generated by ultraviolet photons, lead not only to transient but also to permanent structural changes through the rearrangement of individual molecules. The persistent changes occur near sites with a high density of dangling OD groups that facilitate electron solvation. We conclude that energy dissipation during solvation triggers permanent molecular rearrangement via vibrational excitation.
CRIS-Team Scopus Importer:2020-03-13

Vibrationally dependent electron-electron interactions in resonant electron transport through single-molecule junctions - Erpenbeck, André; Haertle, R.; Bockstedte, Michel Georg; Thoss, Michael (Physical Review B, 2016)
We investigate the role of electronic-vibrational coupling in resonant electron transport through single-molecule junctions, taking into account that the corresponding coupling strengths may depend on the charge and excitation state of the molecular bridge. Within an effective-model Hamiltonian approach for a molecule with multiple electronic states, this requires to extend the commonly used model and include vibrationally dependent electron-electron interaction. We use Born-Markov master equation methods and consider selected models to exemplify the effect of the additional interaction on the transport characteristics of a single-molecule junction. In particular, we show that it has a significant influence on local cooling and heating mechanisms, it may result in negative differential resistance, and it may cause pronounced asymmetries in the conductance map of a single-molecule junction.
UnivIS-Import:2017-12-18:Pub.2016.nat.dphy.ITP.ppem.vibrat